Implementation of an antibiotic stewardship programme in the intensive care unit of a public hospital in Santa Elena - Ruales Carrión, Pablo; Mariscal Santi, Walter; Jiménez Jiménez, William (Revista Universidad de Guayaquil, 2021)
The implementation of Antibiotic Stewardship Programs (PROA for its Spanish acronym) seeks to increase the safety of patients through an adequate use of antibiotics through various microbiological determinations of resistance of microorganisms to the antibiotics selected for this study. In the present work, the implementation of a PROA was carried out in a Hospital of the Province of Santa Elena (Ecuador), evaluating the amount of antibiotic consumed between 2018 and 2019. In 2018 it was observed that Ampicillin + Sulbactam and Piperacillin + tazobactam had Percentages of consumption between 17 and 31% respectively, while in 2019 there was an increase of 19% for Ampicillin + Sulbactam and 41% for Piperacillin + tazobactam. This situation was since the PROA executed generated a de-escalation and reduced the administration of carbapenems such as Meropenem and Imipenem + Cilastatin by other types of antibiotics with less toxicity such as beta-lactam inhibitors. A similar situation occurred with third and fourth generation cephalosporins such as: ceftazidime (of notable use against Pseudomonas aeruginosa and non-fermenting bacilli), ceftriaxone and cefepime, whose uses had a slight increase due to the de-escalation of carbapenems.
Keywords: Bacterial Resistance; Antibiotic Stewarship Program; Antibiotic Selection; De- escalation